Lipid yields from oleaginous yeasts isolated from the north peruvian andes by culture media non-limiting nitrogen - Alexander M.P.C. (2021)
To the National Council of Science, Technology and Technological Innovation (CONCYTEC) and Active Science of Peru, for providing the resources that allowed the realization of this research (Agreement N? 165-2017-FONDECYT).